Impact of Unilateral Coercive Measures on Implementation of the 2030 Agenda in the Republic of Belarus - O. N. Leshenyuk (Международная аналитика)
The aim of this research is to provide a comprehensive analysis of the impact of unilateral coercive measures on sustainable development processes in the Republic of Belarus, as well as their influence on the implementation of the 2030 Agenda in Belarus and the Union State.   Divided into three sections, the article begins by examining how Belarus has adapted its legal framework and state policy to conform to the 2030 Agenda. However, the use of unilateral coercive measures by the collective West to pressure and incentivize “appropriate” behavior, in contradiction of the decisions of the UN Security Council, diverts the country’s resources toward safeguarding its sovereignty and non-intervention in the aff airs of other states. The second section delves into the role of integration associations and the Union State in overcoming coercive restrictive measures. Finally, the third section sheds light on the impact of such measures on the implementation of the 2030 Agenda. Specifi cally, the sectoral sanctions imposed by the US and EU on Belarus in 2021 hinder the development of a common agricultural policy, as well as gas, oil, and petroleum markets of the Union State, while simultaneously creating a fi nancial rift between Belarus and Russia. This underscores the negative eff ects of these measures in the short term.